Robust Sliding Mode Control for T-S Fuzzy Systems via Quantized State Feedback - Xue, Yanmei; Zheng, Bo-Chao; Yu, Xinghuo (IEEE transactions on fuzzy systems, 2018)
This paper is concerned with the robust sliding mode control (SMC) problem for a class of T-S fuzzy systems subject to both matched and mismatched uncertainties. Different from the conventional T-S fuzzy SMC design approach, the quantized states rather than states themselves, are utilized for the control design. By the combination of the proposed zooming-out/zooming-in adjustment policy of the quantizer sensitivity, the quantized state feedback fuzzy sliding mode control scheme is developed to ensure the stabilization of the T-S fuzzy systems. Finally, some simulation results are presented to illustrate the effectiveness of the proposed approach.